A case report of sacrococcygeal foreign body presenting as pilonidal sinus - Anjum, Muhammad Adnan; Ammar , Ahmed Siddique; Naqi, Syed Asghar; Afzal, Ameer; Sarwar, Zeeshan; Ahmed, Rana Sohail (Journal of the Pakistan Medical Association, 2023)
Abstract Pilonidal disease occurs most commonly in those males who have to sit long hours at their work place e.g. online office workers or drivers. It is caused by piercing of broken hairs into the sacrococcygeal region which causes localised inflammation. Inflammation in this area due to any other foreign body is very rare. Among many treatment options for pilonidal sinus, instillation of crystalloid phenol showed promising results in terms of low recurrence rates, low post-operative complications and less healing time. Here, we present the case of a 13-year-old female student who had pilonidal sinus in sacrococcygeal region for six months and was unresponsive to multiple treatments. Later, on exploration it was revealed to contain a small foreign body of 3cm of hard straw of grass. The patient was treated with crystalloid phenol and on regular follow-up she was completely fine by the end of the third week.